2011
DOI: 10.1097/mpg.0b013e3182077d33
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Stool Sample–based Tests for the Diagnosis of Helicobacter pylori Infection in Children

Abstract: Detection of H pylori antigen in stools with ELISA monoclonal antibodies is a noninvasive efficient test for diagnosis of infection in children. One-step tests showed low accuracy and more studies are needed to obtain a useful office-based screening test. The available molecular tests are still unreliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 96 publications
(155 reference statements)
1
54
0
3
Order By: Relevance
“…Recent meta-analysis study on the HpSA test reported that the HpSA test using ELISA polyclonal antibodies had the sensitivity of 92 %, the specifi city of 93 %, LR+ of 16.2, and LR− of 0.09. The monoclonal study also revealed higher diagnostic accuracy in children with sensitivity of 97 %, specifi city of 97 %, LR+ of 29.9, and LR− of 0.03 [ 8 ]. Additionally, another recent meta-analysis in 2014 reported similar diagnostic accuracy of the EIA-based HpSA test in children, reporting an overall pooled sensitivity of 92.1 %, specifi city of 94.1 %, LR+ of 17.01, and LR− of 0.08 [ 9 ].…”
Section: Diagnostic Accuracy Of H Pylori Stool Antigen Test In Untrementioning
confidence: 88%
See 1 more Smart Citation
“…Recent meta-analysis study on the HpSA test reported that the HpSA test using ELISA polyclonal antibodies had the sensitivity of 92 %, the specifi city of 93 %, LR+ of 16.2, and LR− of 0.09. The monoclonal study also revealed higher diagnostic accuracy in children with sensitivity of 97 %, specifi city of 97 %, LR+ of 29.9, and LR− of 0.03 [ 8 ]. Additionally, another recent meta-analysis in 2014 reported similar diagnostic accuracy of the EIA-based HpSA test in children, reporting an overall pooled sensitivity of 92.1 %, specifi city of 94.1 %, LR+ of 17.01, and LR− of 0.08 [ 9 ].…”
Section: Diagnostic Accuracy Of H Pylori Stool Antigen Test In Untrementioning
confidence: 88%
“…The test is very easy to perform and suitable as a one-step in-offi ce test because it takes only 5-15 minutes to interpret the test results grossly without any expensive equipment or skilled personnel. However, diagnostic accuracy of the rapid HpSA test is similar or a bit lower than the conventional HpSA test [ 16 ], with sensitivity of 88 %, specifi city of 93 %, LR+ of 10.6, and LR− of 0.11, according to a recent meta-analysis study [ 8 ]. Therefore, this rapid HpSA test has some limitations in clinical practice despite its convenience.…”
Section: H Pylori Stool Antigen Test Based On Immunochromatographymentioning
confidence: 95%
“…According to a recent meta-analysis study on HpSA testing in children, diagnostic accuracy of ELISA monoclonal antibody revealed the best performance with pooled sensitivity of 97 %, specifi city 97 %, LR+ of 29.9, and LR-of 0.03 [ 28 ]. On the other hand, HpSA test using ELISA polyclonal antibody had relatively lower accuracy with a sensitivity of 92 %, specifi city of 93 %, LR+ of 16.2, and LR-of 0.09, with high heterogeneity [ 28 ].…”
Section: H Pylori Stool Antigen Test In Childrenmentioning
confidence: 96%
“…The systematic review and meta-analysis conducted by Leal et al [56] established that stool ELISA using monoclonal antibodies is an efficient noninvasive test for the diagnosis of H. pylori infection in children.…”
Section: Stool Antigen Testsmentioning
confidence: 99%